The phytogenetic resources: an option for the agricultural development in the American Tropics. - Morera, Jorge A. (1994)
The Central American agriculture shows a low productivity in most of the cultivated crops, apparently due to a lack of improved varieties and a reduced used of cultural practices. The Central American region has climatic, topographic, edaphic and social characteristics that could allow a more integral development and exploitation of the autochthonous phytogenetic resources. Nonetheless, in spite of the significance that it has to the farmer and the industry, there is little research and information on the use and of cultural practices of some potential species of American origin. A better knowledge of the genetic diversity, seasonal production, quality, supply and demand of the products, will allow for the preparation of a list of the phytogenetic potential which is still preserved. The most important incentive of any crop is its economic profitability. On this way, the economic factor promotes the basis for developing an increased production, improve quality and open new alternatives to the farmer and the industry. If a new crop is not profitable, it is rejected inmediately; but on the other hand, if a crop is highly profitable, it is almost imposible to restrain its diffusion. The recognition and conscience drawn by the reasonable use of the "genetic resources" on the national, regional and world level, as an essential base for a dynamic and rational agriculture, by far justifies the programs of the countries in the American Tropics to join their efforts in the preservation and promotion of the genetic diversity.